Effect of Maltodextrin and Soy Protein Isolate on the Physicochemical and Flow Properties of Button Mushroom Powder - Shams, Rafeeya; Singh, Jagmohan; Dash, Kshirod K.; Dar, Aamir Hussain; Nayik, Gulzar Ahmad; Ansari, Mohammad Javed; Hemeg, Hassan A.; Ahmed, Abdelhakam Esmaeil Mohamed; Shaikh, Ayaz Mukarram; Kovács, Béla (Frontiers in Nutrition, 2022)
In this investigation effect of different drying techniques like freeze drying and cabinet drying with two different carrier agents such as maltodextrin and soy protein isolate (SPI) at different levels (10, 15 and 20%) on button mushroom has been revealed. The results revealed that button mushroom powders (BMP) formulated with SPI as a carrier agent had significantly higher powder yield, hygroscopicity, L*, a*, and b* values, whereas BMP formulated with maltodextrin had significantly higher water activity, solubility index, tapped density, bulk density, and flowability. The highest retention of bioactive compounds was reported in freeze-dried mushroom powder as compared to cabinet dried powder using SPI as a carrier agent. The FTIR analysis confirmed that certain additional peaks were produced in mushroom button powder with SPI (1035-3271 cm-1) and maltodextrin (930-3220 cm-1). Thus, the results revealed that SPI had shown promising results for formulating button mushroom powder using freeze drying technique.